Velopharyngeal Dysfunction - Woo, Albert S. (Seminars in Plastic Surgery, 2012)
Velopharyngeal dysfunction (VPD) is a generic term which describes a set of disorders resulting in the leakage of air into the nasal passages during speech production. As a result, speech samples can demonstrate hypernasality, nasal emissions, and poor intelligibility. The finding of VPD can be secondary to several causes: anatomic, musculoneuronal, or behavioral/mislearning. To identify the etiology of VPD, patients must undergo a thorough velopharyngeal assessment comprised of perceptual speech evaluation and functional imaging, including video nasendoscopy and speech videofluoroscopy. These studies are then evaluated by a multidisciplinary team of specialists, who can decide on an optimal course for patient management. A treatment plan is developed and may include speech therapy, use of a prosthetic device, and/or surgical intervention. Different surgical options are discussed, including posterior pharyngeal flap, sphincter pharyngoplasty, Furlow palatoplasty, palatal re-repair, and posterior pharyngeal wall augmentation.
Keywords: velopharyngeal dysfunction; insufficiency; cleft palate; hypernasal speech